Technical Assistance and Training in Integrated Provincial Planning : Quang Nam Province, Vietnam - World Bank (Washington, DC, 2013)
Traditionally both national and regional development planning in Vietnam has been driven by 'top-down' Central Government social and economic targets based on limited analytical investigation. However, with the advent of the free market economy in Vietnam since the late 1980s, vigorous global economic competitiveness and Vietnam's membership to the World Trade Organization (WTO), changes in national policy in Vietnam have now required a more decentralized approach to development planning based on the preparation of integrated regional development strategies. This change in policy direction requires the application of new and innovative approaches to development planning underpinned by 'best practice' tools and techniques. This new way of planning will more effectively manage current and future investment opportunities at the provincial and regional levels in Vietnam. This report is the culmination of the findings and recommendations of the project over this three month period noting that the training program itself involved a total of 45 participants from relevant provincial government and district level authorities in Quang Nam Province (QNP). Appendix two is a list of participants. It is emphasized that the method of training adopted in this technical assistance project was very interactive, it required individual and group tasks to be completed by participants based on the organization of participants into five teams, nomination of a team leader for each team and regular presentations of team activities to the whole group throughout the training program. The program ran for a total of seven days (7-9 October 2008 and 4-6 November 2008) with a 'report back' workshop session of all participants and other provincial government officials on 7 November 2008.